Develop a formative assessment protocol to examine the practice of Popping dance in students online learning - Ling, Xi; Yang, Zhi; Wei, Ming Tao; Bai, Yu Jie; Yuan, Ye; Cui, Yan Shuo; Li, Bin Bin (Frontiers in Education, 2023)
The present article presents an innovative and versatile approach to formative assessment that allows educators to assess students’ aptitude for online learning and their mastery of Popping dance. Popping dance, a form of breakdance, is increasingly being taught through distance learning programs. Despite the growing interest in Popping dance culture across different regions worldwide, few studies have focused on developing a comprehensive formative assessment model that combines Popping dance abilities and online learning. Therefore, we have developed a novel formative assessment framework for Popping dance students, which utilizes various online formats and offers a diversified assessment model. The article outlines five distinct assessment methods with practical examples that can enable students in heavily impacted areas to improve their Popping dance technique at home. These assessment methods cover software operation, theory testing, and technical testing, all of which are suitable for online use. While this model is still in its early stages, it provides a fundamental methodological framework for assessing the Popping dance proficiency of students.